Surface display of eugenol oxidase and dioxygenase complex as a sustainable biocatalyst for efficient bioconversion of lignin-derived 4-n-propylguaiacol to vanillin - Yongqing Tian; Yige Yang; Minmin Ni; Jing Wo (Microbial Cell Factories)
Abstract Background Vanillin is a widely utilized flavor compound of significant value in the food and pharmaceutical sectors, which can be obtained through natural extraction, chemical synthesis, or biotechnological processes. However, the yield from vanilla pods is insufficient to meet market demand, and chemically synthesized vanillin not only encounters limitations in its application within the food and pharmaceutical industries but also needs to address environmental concerns and unsustainable raw material sources. Hence, it is imperative to explore alternative approaches to develop an efficient and cost-effective green vanillin. To address the challenges encountered in vanillin biosynthesis, such as substrate uptake limitations and product-induced inhibition of cell growth,we leveraged the advantages of surface display technology and artificial multi-enzyme scaffolds to construct a hybrid surface-display biocatalytic system by assembling Eugenol oxidase (EUGO) and dioxygenase (NOV1), which can convert lignin biowaste 4-n-propylguaiacol (4-PG) into vanillin on the surface of Escherichia coli BL21(DE3). Results To assemble bioactive macromolecules of EUGO and NOV1 on the surface of E. coli BL21(DE3), we utilized Lpp-OmpA-SpyCatcher (LOAS) as an anchoring motif and displayed EUGO-linker-NOV1-SpyTag (ELNS) by covalent interaction between SpyTag andSpyCatcher to allow their spatial proximity. After optimization of the reaction system, our self-assembly display system exhibited highly efficiency in converting 4-PG into vanillin and reached a final concentration of vanillin at 12.58 g/L, 2.5 times higher than that achieved by thewhole-cell biocatalytic system. The LOAS-ELNS display system was applied to the sustainable biosynthesis of vanillin from lignin-derived 4-n-propylguaiacol at least 10 times. Conclusions This work provided a generalized approach to co-expressing proteins and offered an efficient, eco-friendly, and renewable method for the biosynthesis of vanillin from 4-PG.